Prerequisites for an Artificial Self - Hafner, Verena V.; Loviken, Pontus; Pico Villalpando, Antonio; Schillaci, Guido (Frontiers in Neurorobotics, 2020)
Traditionally investigated in philosophy, body ownership and agency - two main components of the minimal self - have recently gained attention from other disciplines, such as brain, cognitive and behavioural sciences, and even robotics and artificial intelligence. In robotics, intuitive human interaction in natural and dynamic environments becomes more and more important, and requires skills such as self-other distinction and an understanding of agency effects. In a previous review article, we investigated studies on mechanisms for the development of motor and cognitive skills in robots (Schillaci et al., 2016). In this review article, we argue that these mechanisms also build the foundation for an understanding of an artificial self. In particular, we look at developmental processes of the minimal self in biological systems, transfer principles of those to the development of an artificial self, and suggest metrics for agency and body ownership in an artificial self.